2020
DOI: 10.1109/access.2020.3025812
|View full text |Cite
|
Sign up to set email alerts
|

3D Fragmentation Metric and RCSA Scheme for Space Division Multiplexing Elastic Optical Networks

Abstract: The space division multiplexing elastic optical networks (SDM-EONs) based on multi-core fiber (MCF) are an effective solution to improve transmission capacity. In SDM-EONs, spectrum resources take on three-dimensional (3D) properties (i.e., frequency, time, and space), which brings new spatial constraints to network resource allocation. Meanwhile, the spectrum fragmentation in the network also present same characteristics with the setup and release of dynamic lightpath. To improve the success rate of transmiss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…The methods, metrics, and algorithms proposed for EONs cannot be directly applied in SS-FONs due to the introduced additional spatial dimension, especially when lane changes are possible. To the best of our knowledge, fragmentation metrics were studied in SS-FONs only in [23][24][25][26][27][28][29]. However, in these papers, the lane changes were not considered.…”
Section: Related Workmentioning
confidence: 99%
“…The methods, metrics, and algorithms proposed for EONs cannot be directly applied in SS-FONs due to the introduced additional spatial dimension, especially when lane changes are possible. To the best of our knowledge, fragmentation metrics were studied in SS-FONs only in [23][24][25][26][27][28][29]. However, in these papers, the lane changes were not considered.…”
Section: Related Workmentioning
confidence: 99%
“…The authors of [29] showed a multi-features weighted scheme including path lengths, link-spectrum utilization, and other features. The authors of [30][31][32][33] focused on fragmentation in the spectrum to optimize RMSA, where perceptible fragmentation and defragmentation can usefully reduce spectrum fragmentation. However, the above works were unable to achieve real-time RMSA allocation because they only apply fixed RMSA strategies without considering comprehensive perceptions of the EON state.…”
Section: Introductionmentioning
confidence: 99%